2023
DOI: 10.1002/jum.16201
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Temporal Assessment of Changes in Tendon Stiffness Following Rotator Cuff Repair

Abstract: Objectives-How the material properties of the human supraspinatus tendon change following arthroscopic rotator cuff repair is undetermined. Shear wave elastography ultrasound is a relatively new, noninvasive measure of tissue stiffness. We aimed to evaluate any temporal changes in stiffness and/or thickness of supraspinatus tendons in humans following primary arthroscopic rotator cuff repair.Methods-Shear wave elastography was performed at three predetermined regions by a single sonographer at 1-, 6-, 12-, 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
4
2
Order By: Relevance
“…15 Another study performed at our institution found that the stiffness of supraspinatus tendons repaired without patches increased by 21% from 1 week to 6 months postoperatively (P < .001) and stabilized out to 12 months postoperatively. 9 However, the SWE stiffness of the tendon in this study remained unchanged at 6 m/s-which is lower than the average of 8 m/s in tendinopathic tendons-and 10 m/s in healthy tendons. 8 We did not identify any differences in patient-rated or surgeon-measured outcomes between patients with workers' compensation approval for revision rotator cuff repair who received a bioinductive implant versus those who did not at 6 months postoperatively.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…15 Another study performed at our institution found that the stiffness of supraspinatus tendons repaired without patches increased by 21% from 1 week to 6 months postoperatively (P < .001) and stabilized out to 12 months postoperatively. 9 However, the SWE stiffness of the tendon in this study remained unchanged at 6 m/s-which is lower than the average of 8 m/s in tendinopathic tendons-and 10 m/s in healthy tendons. 8 We did not identify any differences in patient-rated or surgeon-measured outcomes between patients with workers' compensation approval for revision rotator cuff repair who received a bioinductive implant versus those who did not at 6 months postoperatively.…”
Section: Discussioncontrasting
confidence: 61%
“…6,11,16,20 Ultrasound Assessment All assessments of rotator cuff repair integrity and SWE stiffness of the supraspinatus tendon were performed on an ultrasound system with virtual touch imaging quantification elastography (Siemens Acuson S3000 HELIX Evolution ultrasound system with Virtual Touch IQ; Siemens Medical Solutions) with a linear 9L4 MHz transducer, per previously validated protocols. 4,9,21 A single sonographer (L.H.) with 25 years of experience in shoulder ultrasound performed all assessments.…”
Section: Data Collectionmentioning
confidence: 99%
“…The SWE values of the stiffness of the healing rotator cuff tendon presented in our study may help guide clinical practice, especially postoperative patient rehabilitation. This study demonstrated that the repaired supraspinatus tendon 21 Adaptations are themselves works protected by copyright. So in order to publish this adaptation, authorization must be obtained both from the owner of the copyright in the original work and from the owner of copyright in the translation or adaptation.…”
Section: Discussionmentioning
confidence: 62%
“…The strength of this present study was that all patients were prospectively recruited and assessed in a systematic fashion. All patients were treated by a single surgeon, using a single-row arthroscopic rotator cuff repair technique, and assessed by a single musculoskeletal sonographer, each with over 25 years of experience in arthroscopic shoulder surgery and shoulder ultrasound respectively, improving the internal 21 Adaptations are themselves works protected by copyright. So in order to publish this adaptation, authorization must be obtained both from the owner of the copyright in the original work and from the owner of copyright in the translation or adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation